2011
DOI: 10.1111/j.1469-8749.2011.03990.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a supported speed treadmill training exercise program on impairment and function for children with cerebral palsy

Abstract: Aim  To compare the effects of a supported speed treadmill training exercise program (SSTTEP) with exercise on spasticity, strength, motor control, gait spatiotemporal parameters, gross motor skills, and physical function. Method  Twenty‐six children (14 males, 12 females; mean age 9y 6mo, SD 2y 2mo) with spastic cerebral palsy (CP; diplegia, n=12; triplegia, n=2; quadriplegia n=12; Gross Motor Function Classification System levels II–IV) were randomly assigned to the SSTTEP or exercise (strengthening) group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
98
0
37

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(152 citation statements)
references
References 39 publications
0
98
0
37
Order By: Relevance
“…Treadmill training is believed to contribute to postural control by allowing multiple repetitions of the steps of the gait cycle in a rhythmic pattern, thereby improving control between agonist and antagonist muscles and resulting in improved functional and static balance. Previous studies have demonstrated positive results from treadmill training on gait speed and endurance, gross motor function and cardiorespiratory fitness [15][16][17][18][19][20][21] . However, these studies do not address the possible effects of treadmill training on postural stability (static and functional balance).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Treadmill training is believed to contribute to postural control by allowing multiple repetitions of the steps of the gait cycle in a rhythmic pattern, thereby improving control between agonist and antagonist muscles and resulting in improved functional and static balance. Previous studies have demonstrated positive results from treadmill training on gait speed and endurance, gross motor function and cardiorespiratory fitness [15][16][17][18][19][20][21] . However, these studies do not address the possible effects of treadmill training on postural stability (static and functional balance).…”
Section: Introductionmentioning
confidence: 98%
“…Different approaches have been used to favor selective control and the coordination of muscle contrations during gait [13][14][15] . In recent years, locomotor training on a treadmill has been used in the treatment of children with CP in an attempt to maximize orthostatism and gait velocity [15][16][17][18][19][20][21] . Treadmill training is believed to contribute to postural control by allowing multiple repetitions of the steps of the gait cycle in a rhythmic pattern, thereby improving control between agonist and antagonist muscles and resulting in improved functional and static balance.…”
Section: Introductionmentioning
confidence: 99%
“…Spasticity causes wide range of ambulatory disorders which explains the individual difficulties in maintaining and restores both static and dynamic balance [25]. There is a strong relationship between balance and single leg support time which indicated as test to measure the upright postural stability after upper motor neuron lesion [26]. Further studies are also needed for determining more differences in the biomechanical strategies adopted by different types and severities of the cerebral palsy in order to develop better training programs.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, locomotor training on a treadmill widely uses in the treatment of children with CP [16]. Functional electrical stimulation (FES) has been used to enhance the effect of locomotor training [15].…”
Section: Introductionmentioning
confidence: 99%